Functional Unit Classifiers in (Non)-Classifier Russian - Keren Khrizman (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
It has often been argued that functional individuating classifiers and plural count nouns ought to be in complementary distribution (e.g. Borer 2005, Chierchia 2010). This apparently works neatly for Chinese and English. Russian, however, is an interesting case. On the one hand it has count nouns which can be directly modified by numerals. On the other hand it has three classifiers, štuka ‘item’, čelovek ‘person’ and golova ‘head’, which optionally occur in numeral constructions with plural nouns and look very much like functional individuating classifiers (cf. Sussex 1976, Yadroff 1999). I show that a closer look at the data reveals that apparently count constructions using these optional classifiers have properties of measure constructions such as five liters of water. Based on that I argue that these classifiers are not individuating classifiers but are measure words which measure mass denotations in terms of natural units in the sense of Krifka (1989, 1995).
Keywords: Russian language; classifiers; functional units; numeral constructions; count constructions; individuating classifiers